Low parasite load estimated by qPCR in a cohort of children living in urban area endemic for visceral leishmaniasis in Brazil. - Letícia Helena dos Santos Marques; Luciana Inácia Gomes; Iara Caixeta Marques da Rocha; Thaís Almeida Marques da Silva; Edward Oliveira; Maria Helena Franco Morais; Ana Rabello; Mariângela Carneiro (Public Library of Science (PLoS), 2012)
BACKGROUND: An important issue associated with the control of visceral leishmaniasis is the need to identify and understand the relevance of asymptomatic infection caused by Leishmania infantum. The aim of this study was to follow the course of asymptomatic L. infantum infection in children in an area of Brazil where it is endemic. The children were assessed twice during a 12-month period. METHODOLOGY: In this population study, 1875 children, ranging from 6 months to 7 years of age, were assessed. Blood samples were collected on filter papers via finger prick and tested by ELISA (L. infantum soluble antigen and rk39). Seropositives samples (n = 317) and a number of seronegatives samples (n = 242) were subjected to qPCR. After 12 months, blood samples were collected from a subgroup of 199 children and tested for Leishmania spp. to follow the course of infection. PRINCIPAL FINDINGS: At baseline qPCR testing identified 82 positive samples. The prevalence rate, as estimated for 1875 children based on the qPCR results, was 13.9%. The qPCR testing of whole blood samples collected from a cohort of children after 12 months (n = 199) yielded the following results: of the 44 (22.1%) children with positive qPCR results at baseline, only 10 (5.0%) remained positive, and 34 (17.1%) became negative; and of the 155 (77.9%) children with negative qPCR results, 131 (65.8%) remained negative, and 24 (12.1%) became positive at the follow-up measurement. The samples with positive findings at baseline (n = 82) had a mean of 56.5 parasites/mL of blood; and at follow-up the mean positive result was 7.8 parasites/mL. CONCLUSIONS: The peripheral blood of asymptomatic children had a low and fluctuating quantity of Leishmania DNA and a significant decrease in parasitemia at 1-year follow-up. Quantitative PCR enables adequate monitoring of Leishmania infection.